2017
DOI: 10.1371/journal.pone.0183104
|View full text |Cite
|
Sign up to set email alerts
|

Improved usability of a multi-infusion setup using a centralized control interface: A task-based usability test

Abstract: The objective of this study was to assess the usability benefits of adding a bedside central control interface that controls all intravenous (IV) infusion pumps compared to the conventional individual control of multiple infusion pumps. Eighteen dedicated ICU nurses volunteered in a between-subjects task-based usability test. A newly developed central control interface was compared to conventional control of multiple infusion pumps in a simulated ICU setting. Task execution time, clicks, errors and questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…2 for an example) [4655], (2) displays that integrated data from bedside devices and monitors (see Fig. 3) [5661], (3) displays that integrated data for the purpose of antibiotic selection and management [62–64], and (4) displays that integrated information into a novel graphical presentation [6568]. Display designers frequently described an intention to organize the information in more clinically meaningful ways, for example, by human body systems, medical concepts, or provider tasks.…”
Section: Resultsmentioning
confidence: 99%
“…2 for an example) [4655], (2) displays that integrated data from bedside devices and monitors (see Fig. 3) [5661], (3) displays that integrated data for the purpose of antibiotic selection and management [62–64], and (4) displays that integrated information into a novel graphical presentation [6568]. Display designers frequently described an intention to organize the information in more clinically meaningful ways, for example, by human body systems, medical concepts, or provider tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, while nurses provide a unique end-user-centric, patient-focused approach to medical device development, there is little evidence of their involvement during device development [ 37 ]. This continues to be true at present, especially in the fields of vascular access and infusion therapy, with only a few published cases concerning intravenous syringes and infusion pumps [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result in table 3 also found that the majority of participants expected that the new design of the intravenous system device can be designed to stop automatically. A "This device must have a quality battery so that if the light turn of or when the patient delivered to the radiology room/ physiotherapy room it can still be used without electricity" Theme 4: Simplicity Category Easy to use Participant 13 said: "The device must be easily operated by new nurses without special training" Participant 8 said: "The device must be designed in a sophisticated yet simple way to operate" study stated that the infusion pump must have the ability to stop the infusion fluid that runs out automatically (Doesburg et al, 2017). Other nurses in this study expected that the new design of the device also to be able to monitor the remaining intravenous fluid automatically through the screen of the device.…”
Section: Discussionmentioning
confidence: 99%